BS EN 1793-6 AMD1. Road traffic noise reducing devices. Test method for determining the acoustic performance. Part 6. Intrinsic characteristics. In situ values of airborne sound insulation under direct sound field conditions (8th October 2019) - British Standards Institution,
No abstract available